Iterative learning control for over-determined, under-determined, and ill-conditioned systems - Avrachenkov, Konstantin E.; Longman, Richard W. (Zielona Góra: Uniwersytet Zielonogórski)
This paper studies iterative learning control (ILC) for under-determined and over-determined systems, i.e., systems for which the control action to produce the desired output is not unique, or for which exact tracking of the desired trajectory is not feasible. For both cases we recommend the use of the pseudoinverse or its approximation as a learning operator.
Keywords: iterative learning control; over-determined; under-determined; ill-conditioned systems; pseudoinverse